Tucumã (Astrocaryum aculeatum) extract: phytochemical characterization, acute and subacute oral toxicity studies in Wistar rats. (4th March 2022) - Guex, Camille Gaube; Cassanego, Gabriela Buzatti; Dornelles, Rafaela Castro; Casoti, Rosana; Engelmann, Ana Martiele; Somacal, Sabrina; Maciel, Roberto Marinho; Duarte, Thiago; Borges, Warley de Souza; Andrade, Cínthia Melazzo de; Emanuelli, Tatiana; Danesi, Cristiane Cademartori; et al.
Abstract: Natural products are often used by the population to treat and/or prevent several disorders. Tucumã is an Amazonian fruit widely consumed by local population and no in vivo toxicity studies regarding its safety are available in the literature to date. Therefore, the phytochemical characterization, acute and repeated dose 28-day oral toxicities of crude extract of tucumã's pulp (CETP) in Wistar rats were evaluated. For the CETP preparation, tucumã pulp was crushed and placed into sealed amber glass jars containing absolute ethanol solution for extraction. CETP phytochemical analyses evidenced the presence of carotenoids, flavonoids, unsaturated and satured fatty acids, and triterpenes. In the acute toxicity, female rats from the test group were treated with CETP at single dose of 2000 mg/kg. For the repeated dose toxicity, CETP was administered to male and female rats at doses of 200, 400 and 600 mg/kg, for 28 days. Body weight was recorded during the experiment and blood, liver and kidney were collected for further analysis. No mortality or toxicity signs were observed during the studies. CETP was classified as safe (category 5, OECD guide), in acute toxicity. In repeated dose study was observed alterations in some biochemical parameters, as well as in oxidative damage and enzymatic activity. Histopathological findings showed renal damage in male rats at higher dose. The data obtained suggest that CETP did not induced toxicity after exposure to a single or repeated doses in female rats. However, in males may be considered safe when given repeatedly in low doses.